ا‫ثر ‬‫الجماعات‬ ‫المرجعية‬ ‫على‬ ‫القرارات‬ ‫الشرائية‬ ‫للسلع‬ ‫المعمرة‬ ‫دراسة‬‫ميدانية‬ ‫بوكالة‬ ‫رونو‬ ‫للسيارات‬ ‫بولاية‬ ‫سوق‬ ‫أهراس‬ - نواري ‫ ‬‫آمال‬; ‫قنادزية ‬‫دليلة (My University, 2017)
The current research examined concepts related to the nature of purchasing decisions, its mechanisms of selection, and evaluation methods. The study depicted the types of reference groups that affect the consumer's purchasing decision of goods at Renault Motor Agency in the State of Souk Ahras, indicating the different factors that influence the consumer's behavior and decision making. The following investigation was based on a randomly selected sample of 40 individuals. The results demonstrated that reference groups affect the consumer's decision when purchasing a car, however, there arestatistical differences related to the degrees of impact of reference groups on the consumer's purchasing decision. .